2012
DOI: 10.1007/s00347-012-2649-1
|View full text |Cite
|
Sign up to set email alerts
|

Fundusscreening durch Assistenzpersonal

Abstract: Ocular fundus photography allows detection of both ocular and systemic diseases. This study investigated the efficacy of a broad screening in a department of internal medicine using nonmydriatic digital fundus photography. For 8 weeks a medical technician was trained in using the camera as well as interpreting the photographs. The medical technician and an ophthalmologist evaluated the fundus photographs separately by using a self-developed questionnaire. The fundus camera was user-friendly and after several w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…One might argue that for diabetic retinopathy screening an ophthalmologist is essential and digital fundus imaging alone might not be sufficient. However, recent studies comparing nonophthalmologists with ophthalmologists for the diagnosis of DR have shown similar accuracy in the detection of changes of the fundus even with paramedical staff performing the screening procedure [ 25 , 38 40 ]. This was also the case in the study presented here.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One might argue that for diabetic retinopathy screening an ophthalmologist is essential and digital fundus imaging alone might not be sufficient. However, recent studies comparing nonophthalmologists with ophthalmologists for the diagnosis of DR have shown similar accuracy in the detection of changes of the fundus even with paramedical staff performing the screening procedure [ 25 , 38 40 ]. This was also the case in the study presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the fundus photography by a reference ophthalmologist revealed that no change of diagnoses of DR categories was necessary (data not shown). Furthermore, several studies have evaluated the sensitivity and specificity of digital fundus screening [ 20 , 41 ], showing that instant fundus screening by trained nonophthalmologists was accurate and safe in the detection of DR [ 25 , 42 ]. However, since the number of detected DRs in this study is clearly higher than preexistent DRs, it seems unlikely that a remarkable proportion of patients with DR might have been missed in the study although this cannot be fully excluded, since stereoscopic colour fundus photographs as gold standard were not used in this evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fundus screening allows detection of both ocular and systemic diseases that is diabetes, glaucoma, cataract, age-related macular degeneration (AMD) and other causes [11]. In this paper, data sets consisting of retinal images labelled as normal, cataracts, age-related macular degeneration and myopia are used to understand the effect of increasing the number of fully-connected layers in a Convolutional Neural Network.…”
Section: Ocular Diseasesmentioning
confidence: 99%